Child-Friendly Justice – French Perspective - Nord-Wagner, Magalie (Child-Friendly Justice. The Participation and the Rights of the Child in Court Proceedings From a Central European Comparative Perspective, 2025)
Abstract:Children’s participation rights in France are not explicitly in the Constitution but are secured through international conventions (CRC, European texts), national laws, and the juvenile justice system. The key concept is discernement, combined with age thresholds, which determine when minors can be heard, take part in proceedings, or be held responsible. Civil, administrative, and criminal procedures provide representation (parents, guardians, ad hoc administrators) and specific guarantees: specialised courts, compulsory legal counsel, audiovisual recorded hearings, and priority for educational over punitive measures. France also develops child friendly justice with simplified guides, adapted spaces (Mélanie rooms, UAPED), and specialised training. The Conseil Constitutionnel and the Défenseur des droits ensure that the best interests of the child and proportional treatment remain central.Keywords:Children’s rights, Juvenile justice, Discernement, Age thresholds, Child-friendly justice, Constitutional guarantees